Brain metastases from rectal cancer – case report - Litak, Jakub; Kamiński, Maciej; Budny, Agnieszka; Grochowski, Cezary; Litak, Joanna; Kamieniak, Piotr (Journal of Education, Health and Sport, 2017)
Colorectal  origin of  brain metastases (BM) are relatively  rare in oncological practice.  Represent 0,6% to 3,2% of all brain metastatic lesions with median survival time of 2.8–5.4 months. Only very few patients survive more than 1 year. Metastases spread to the brain reflecting  the vascular anatomy.  Colorectal metastases appear early and more frequently  in pulmon and liver. BM use to be called late metastases. Thanks to highier availability of diagnostic methods as a CT or MRI detectability of BM  raised significantly. Early diagnosis and treatment of BM  provide proper quality of life for patient  ,  in addition to adequate control of prime colorectal cancer.